A SURVEY ON THE CURES FOR THE CURSE OF DIMENSIONALITY IN BIG DATA - Remesh, Reshma; V, Pattabiraman. (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Dimensionality reduction techniques are used to reduce the complexity for analysis of high dimensional data sets. The raw input data set may have large dimensions and it might consume time and lead to wrong predictions if unnecessary data attributes are been considered for analysis. So using dimensionality reduction techniques one can reduce the dimensions of input data towards accurate prediction with less cost. In this paper the different machine learning approaches used for dimensionality reductions such as PCA, SVD, LDA, Kernel Principal Component Analysis and Artificial Neural NetworkÂ have been studied.